Understanding the Effects of Anion Interactions with Ag Electrodes on Electrochemical CO2 Reduction in Choline Halide Electrolytes. Issue 12 (20th May 2021) - Garg, Sahil; Li, Mengran; Wu, Yuming; Nazmi Idros, Mohamed; Wang, Hongmin; Yago, Anya Josefa; Ge, Lei; Wang, Geoff G. X.; Rufford, Thomas E.
Abstract: Interactions of electrolyte ions at electrocatalyst surfaces influence the selectivity of electrochemical CO2 reduction (CO2 R) to chemical feedstocks like CO. We investigated the effects of anion type in aqueous choline halide solutions (ChCl, ChBr, and ChI) on the selectivity of CO2 R to CO over an Ag foil cathode. Using an H‐type cell, we observed that halide‐specific adsorption at the Ag surface limits CO faradaic efficiency (FECO ) at potentials more positive than −1.0 V vs. reversible hydrogen electrode (RHE). At these conditions, FECO increased from I − <Br − <Cl −, that is, in the opposite order to the strength of specific adsorption of the halide ions (Cl − <Br − <I − ). At potentials of −1.0 to −1.3 V vs. RHE, restructuring of the Ag surface in ChI and ChCl via dissolution and re‐electrodeposition led to more CO‐selective Ag facets ([220], [311], and [222]) than in ChBr. This mechanism allowed very high faradaic efficiencies for CO of 97±2 % in ChI and 94±2 % in ChCl to be achieved simultaneously with high current densities at −1.3 V vs. RHE. We also demonstrate that high selectivity to CO (FECO >90 %) in ChCl (at −0.75±0.06 Vvs. RHE) and ChI (at −0.78±0.17 V vs. RHE) could be achieved at a current density of 150 mA cm −2 in a continuous flow‐cell electrolyser with Ag nanoparticles on a commercial gas diffusion electrode. This study provides new insights to understand the interactions of anions with catalysts and offers a new method to modify electrocatalyst surfaces. Abstract : Ag bravely faces CO2 : We revealed that halide anions (especially Cl − and I − ) interactions with the Ag foil creates higher‐index facets via in situ silver‐halide dissolution and redeposition on the foil. These higher‐index facets are more selective for CO2 R to CO whereas the specific adsorption of halide anions on the Ag surface limits the CO2 R‐to‐CO selectivity at more positive potentials.